EFFECT OF PHYSICAL REHABILITATION MEASURES ON CORRECTION OF REACTIVE RESPONSE OF NEUTROPHIC GRANULOCYTES OF PERIPHERAL BLOOD IN CHILDREN WITH AGE 7-17 YEARS WITH SKOLIOUSIS - Дичко, О.А. (World of Medicine and Biology, 2017)
The paper presents the findings on the effect of rehabilitation measures on correction of reactive response of neutrophilic granulocytes of peripheral blood of children with scoliosis of school age (7-17 years). It was established, that the reactive response of the NG is reduced under the influence of rehabilitation measures in boys and girls with scoliosis at the age of 7-17 years, which, from our point of view, is related to the general improvement of the body. This confirms the positive effect of measures on the cellular reactivity of the organism and on the adaptive processes of the organism of children of school age with scoliosis.